A clinical algorithm for same-day HIV treatment initiation in settings with high TB symptom prevalence in South Africa: The SLATE II individually randomized clinical trial - Maskew, Mhairi; Brennan, Alana T.; Fox, Matthew P.; Vezi, Lungisile; Venter, Willem D. F.; Ehrenkranz, Peter; Rosen, Sydney (PLoS medicine, 2020)
Introduction In its 2017 revision of the global guidelines for HIV care and treatment, the World Health Organization (WHO) called for rapid or same-day initiation of antiretroviral therapy (ART) for eligible patients testing positive for HIV [1], with the goal of reducing losses of treatment-eligible patients from care before they receive their first dose of antiretroviral (ARV) medications [2–4]. The algorithm, previously reported in [15] and illustrated in Fig 1, consisted of four screening tools, each evaluating an area of eligibility required for same-day ART initiation: (1) symptom report, (2) medical history, (3) brief physical examination, and (4) patient readiness assessment. Patients were excluded if they were pregnant (pregnancy was an exclusion criterion because treatment guidelines for pregnant women differ from those for nonpregnant adults; most pregnant women are diagnosed with HIV and initiated on ART in antenatal clinics, not general adult HIV clinics); did not intend to return to this clinic for further HIV care in the coming year; refused to be traced by phone or in person for follow-up care if test results received after the enrollment visit indicated that further care was needed; were not physically, mentally, or emotionally able to participate in the study in the opinion of the investigators or study staff; were not willing or able to provide written informed consent to participate in the study; or had previously enrolled in the same study or the SLATE I study. After exclusion of pregnant women, all study participants completed an interviewer-administered questionnaire exploring patients’ demographic characteristics, HIV history, knowledge and treatment preferences, employment and primary activities, and visit costs.